Human genetic selection on the MTHFR 677C>T polymorphism - Rodríguez Alfonso; Gaitán María; Jiménez Ana J; Palomares Arturo R; Callejón Gonzalo; Mayor-Olea Álvaro; Ruiz Maximiliano; Reyes-Engel Armando (BMC, 2008)
Abstract Background The prevalence of genotypes of the 677C>T polymorphism for the MTHFR gene varies among humans. In previous studies, we found changes in the genotypic frequencies of this polymorphism in populations of different ages, suggesting that this could be caused by an increase in the intake of folate and multivitamins by women during the periconceptional period. The aim was to analyze changes in the allelic frequencies of this polymorphism in a Spanish population, including samples from spontaneous abortions (SA). Methods A total of 1305 subjects born in the 20th century were genotyped for the 677C>T polymorphism using allele specific real-time PCR with Taqman® probes. A section of our population (n = 276) born in 1980-1989 was compared with fetal samples (n = 344) from SA of unknown etiology from the same period. Results An increase in the frequency of the T allele (0.38 vs 0.47; p < 0.001) and of the TT genotype (0.14 vs 0.24; p < 0.001) in subjects born in the last quarter of the century was observed. In the 1980-1989 period, the results show that the frequency of the wild type genotype (CC) is about tenfold lower in the SA samples than in the controls (0.03 vs 0.33; p < 0.001) and that the frequency of the TT genotype increases in the controls (0.19 to 0.27) and in the SA samples (0.20 to 0.33 (p < 0.01)); r = 0.98. Conclusion Selection in favor of the T allele has been detected. This selection could be due to the increased fetal viability in early stages of embryonic development, as is deduced by the increase of mutants in both living and SA populations.